(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
Nowadays, the problems related to conveyer rollers in mining production enterprises occurring more often and therefore, it is really crucial to find address to these issues. The conducted studies show that the highest index of displacement caused by the method of installation of roller covers by using the method of roller construction with thread cover, the displacement on the axis of the roller was reduced, that is, the displacements were several times was reduced.